Efficacy of entomopathogenic organisms Beauveria bassiana, Isaria fumosoroseus, Metarhizium anisopliae and Chromobacterium subtsugae against the western flower thrips, Frankliniella occidentalis, under both laboratory and greenhouse conditions - Kivett, Jessica Marie (Kansas State University, 2015)
Western flower thrips (WFT), Frankliniella occidentalis, is one of the most destructive insect pests of greenhouse production systems because of the direct and indirect damage they cause and their ability to develop resistance to a wide variety of insecticides. A common method of avoiding resistance development is by rotating insecticides that have different modes of action. Entomopathogenic organisms (EPO), such as fungi and bacteria, have modes of action that are very different from standard insecticides. Thus, by incorporating EPO into rotation programs, greenhouse producers may preserve the efficacy of insecticides used for suppression of WFT populations. Therefore, the objectives of this study were to 1) determine the efficacy of entomopathogenic fungi on WFT adults and nymphs, and to assess product effectiveness when used beyond the expiration date; 2) evaluate the efficacy of entomopathogenic fungi against WFT nymphs when combined with the insect growth regulator, azadirachtin; and 3) evaluate different rotation programs that include EPO and standard insecticides commonly used to suppress WFT populations. To satisfy objective one and two, a series of laboratory bioassays were conducted in which WFT nymphs and adults were exposed to three entomopathogenic fungi (Beauveria bassiana, Isaria fumosoroseus, and Metarhizium anisopliae) at two label rates (maximum and minimum), and two product conditions (fresh and expired). Furthermore, a bioassay in which each entomopathogenic fungi was tested with and without azadirachtin was conducted to determine if there was any synergistic effect on WFT nymphal mortality. Results indicated that adults are generally more susceptible to infection by entomopathogenic fungi than nymphs, fresh products resulted in higher mortality than expired products, and azadirachtin, when mixed with the entomopathogenic fungi, did not increase mortality of WFT nymphs except when combined with M. ansiopliae. Insecticide rotation programs that included EPO were evaluated by conducting a series of greenhouse experiments in which chrysanthemum, Dendranthema x morifolium plants were artificially infested with WFT adults. Eight-week rotation programs were applied to each plant and weekly counts of adults captured on yellow sticky cards were recorded. A final quality assessment of damage due to WFT feeding on foliage and flowers (1 to 5 in which 1 = no damage, and 5 = greater than 75% damage) was also recorded. In addition, a cost comparison of each rotation program was determined. Generally, insecticide rotations programs which incorporated EPO resulted in no significant difference in WFT populations compared to standard insecticide rotation programs without EPO. Furthermore, there were no significant differences between any of the rotation programs in regards to foliage and flower quality. Based on the results of the cost comparison, there may be a cost savings associated with using EPO. Therefore, by incorporating EPO into insecticide rotation programs, greenhouse producers may reduce costs as well as reduce selection pressure on WFT populations, which may avoid or delay resistance development.
Keywords: Insecticide rotation program; Resistance management; Entomology (0353); Horticulture (0471)